Strategi Pengelolaan Kawasan Hutan Dengan Tujuan Khusus Cemoro Modang Sebagai Kawasan Hutan Berkelanjutan (Management Strategy of The Cemoro Modang Special Purpose Forest Area as A Sustainable Forest Area) - Jatu Diah Kartikasari; Maria Theresia Sri Budiastuti; Chanel Tri Handoko (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2024)
The Cemoro Modang Special Purpose Forest Area (SPFA) plays a vital role in supporting forestry research, education, and training. SPFA Cemoro Modang, as one of the forestry research and development units, has experienced the dynamics of adding area functions as a role model for implementing standard models in the forestry sector. This has led to changes in its forest governance system. It needs new strategies to ensure sustainable forest management, especially in balancing conservation, research, and community engagement. This study identifies several strategic approaches to sustainable management using a SWOT analysis method. Based on the SWOT results, stakeholders are divided into interest quadrants according to their level of influence and interests. The strategic approaches include: (1) fostering partnerships between forest management stakeholders, (2) resolving land use conflicts through inclusive dialogue and mediation, (3) strengthening the capacity of forest managers and local partners, (4) building cross-sectoral collaborations, and (5) optimizing the use of Non-Timber Forest Products (NTFPs) to improve local community livelihoods without sacrificing forest integrity. Stakeholder involvement is the foundation of this strategy. The key stakeholders are Office for Standard Implementation of Environment and Forestry Instruments Solo, which manages the SPFA; State Forestry Public Company Cepu Management Unit, which owns the plant assets; pesanggem, or forest farmers who cultivate forest land; and community groups that partner with SPFA in its management. Through the combination of multi-stakeholder collaboration and strategic management practices, SPFA Cemoro Modang serves as a model for sustainable forest management.